2013
DOI: 10.1136/jmedgenet-2013-101785
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing of Bardet–Biedl syndrome patient identifies a null mutation in the BBSome subunitBBIP1(BBS18)

Abstract: Background Bardet-Biedl Syndrome (BBS) is a recessive and genetically heterogeneous ciliopathy characterized by retinitis pigmentosa, obesity, kidney dysfunction, post-axial polydactyly, behavioral dysfunction and hypogonadism. Seven of the 17 BBS gene products identified to date assemble together with the protein BBIP1/BBIP10 into the BBSome, a protein complex that ferries signaling receptors to and from cilia. Methods and results Exome sequencing performed on a sporadic BBS case revealed for the first time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
92
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 18 publications
0
92
0
2
Order By: Relevance
“…BBS18, which was originally referred to as BBIP10 (for BBSome-interacting protein of 10 kDa), was missed in the initial BBSome isolation (Nachury et al, 2007), but was identified as a component of the BBSome in a subsequent study (Loktev et al, 2008) and has been recently found to be mutated in BBS patients (Scheidecker et al, 2014). However, Loktev et al also reported that BBS18 associates with the BBSome inside the cilium, but not at centriolar satellites (Loktev et al, 2008).…”
Section: Application Of Vip Assay To Determine Ternary and Quaternarymentioning
confidence: 98%
“…BBS18, which was originally referred to as BBIP10 (for BBSome-interacting protein of 10 kDa), was missed in the initial BBSome isolation (Nachury et al, 2007), but was identified as a component of the BBSome in a subsequent study (Loktev et al, 2008) and has been recently found to be mutated in BBS patients (Scheidecker et al, 2014). However, Loktev et al also reported that BBS18 associates with the BBSome inside the cilium, but not at centriolar satellites (Loktev et al, 2008).…”
Section: Application Of Vip Assay To Determine Ternary and Quaternarymentioning
confidence: 98%
“…BBS is a genetically heterogeneous condition for which 19 BBS14/CEP290, BBS15/WDPCP/FRITZ, BBS16/SDCCAG8, BBS17/LZTFL1, BBS18/BBIP10/BBIP1 and BBS19/IFT27; ( [9][10][11][12][13][14] and references within). This heterogeneity was originally thought to be the cause of the significant inter-familial variability that characterizes the syndrome.…”
Section: The Genetics Of Bbsmentioning
confidence: 99%
“…The BBSome is a 438kDa complex composed by eight BBS proteins (BBS1, BBS2, BBS4, BBS5, BBS7, BBS8, BBS9 and BBIP10/BBS18) that functions as a coat for vesicles destined to the cilium [14,47,48]. Furthermore, it has been shown that the BBSome recognizes ciliary targeting signals in cargo proteins thus sorting and trafficking membrane proteins to the primary cilium such as the G protein coupled receptors somatostatin receptor type 3 (Sstr3) and melanin-concentrating hormone receptor 1 (Mchr1) ( Fig.…”
Section: The Bbs Proteins In Ciliogenesis: the Bbsomementioning
confidence: 99%
“…No (39) Bardet-Biedl Syndrome 15 615992 BBS15/WDPCP No (40) Bardet-Biedl Syndrome 16 615993 BBS16/SDCCAG8 Yes (41,42) Senior-Loken Syndrome 7 613615 Id. No (23) Bardet-Biedl Syndrome 17 615994 BBS17/LZTFL1 Yes (43) Bardet-Biedl Syndrome 18 613605 BBS18/BBIP1/BBIP10 Yes (44) Bardet-Biedl Syndrome 19 615996 BBS19/IFT27/RABL4 Yes (45) Meckel Syndrome 6 612284 CC2D2A No (46) Joubert Syndrome 9 612285 Id. No (47) COACH Syndrome 216360 Id.…”
Section: Intraflagellar Transportmentioning
confidence: 99%